Effect of artificial defoliation in dry matter production and accumulation in two soybean cultivars - Pissaia, Amir; Colasante, Luiz Osvaldo; Costa, José Antonio (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted during the 1978/79 growing season at the Agronomic Experimental Station, UFRS, Guaíba, with the objective of determining the effects of defoliation levels of 33, 67 and 100%, applied at development stages V4, R1/R2, R3, R4, R5 and R6, on dry matter accumulation in two soybean cultivars (Glycine max (L.) Merrill), Paraná (early maturity) and Santa Rosa (late maturity). Defoliation levels had different effects upon plant development according to the development stage. Total dry matter accumulation decreased, affected by the increasing levels of defoliation in R3. Seed dry matter accumulation decreased in both cultivars with increasing levels of defoliation at stage R4, due to a progressive competition increase between vegetative and reproductive structures developing simultaneously. The defoliation at stage R5 was most critical in both cultivars.